Screening Nanographene‐Mediated Inter(Porphyrin) Communication to Optimize Inter(Porphyrin–Fullerene) Forces. Issue 17 (11th March 2021) - Haines, Philipp; Kaur, Ramandeep; Martin, Max M.; Minameyer, Martin B.; Frühwald, Stefan; Bönisch, Simon; Lungerich, Dominik; Hampel, Frank; Görling, Andreas; Drewello, Thomas; Jux, Norbert; Guldi, Dirk M.
Abstract: Multifunctional molecular materials comprising porphyrins and fullerenes have served as perfect prototypes to study key aspects of natural photosynthesis starting at light harvesting and energy transfer processes all the way to charge separation, charge shift, and charge recombination. Herein, hexa‐ peri ‐hexabenzocoronenes (HBCs) are explored, decorated with one, two, and six porphyrins at their peripheral positions, within the context of replicating key steps of photosynthesis. The major focus of the investigations is to screen inter(porphyrin) communications across the HBC platform as a function of the substitution pattern and to optimize the intermolecular forces with fullerenes. To this end, the ground‐ and excited‐state features are investigated in the absence of C60 and C70 by employing an arsenal of spectroscopic methods. Further insights into inter(porphyrin) communications come from time‐dependent density‐functional theory (TDDFT) calculations. In the presence of C60 and C70, X‐ray crystallography, steady‐state and time‐resolved spectroscopy, and mass spectrometry corroborate exceptionally strong inter(porphyrin–fullerene) interactions in the solid, liquid, and gas phases. The experiments are backed‐up with DFT calculations of the geometrically optimized and energetically stable complex configuration. Abstract : Herein, the inter(porphyrin) communication of hexa‐ peri ‐hexabenzocoronene (HBC), decorated with one, two, and six porphyrins, is explored. Furthermore, the supramolecular interactions between fullerenes C60 /C70 and HBC–porphyrin conjugates are investigated. Steady‐state and time‐resolved spectroscopies for insolution experiments, X‐ray diffraction for the solid state, and mass spectrometry for the gas phase are used, complemented by time‐dependent density‐functional theory calculations.